Hygrothermische Klimatypen im Raum Puebla-Tlaxcala (Mexiko). Erläuterungen zu einer Klimatypenkarte 1:500 000 - Lauren, Wilhelm; Stiehl, Eckart (ERDKUNDE, 1972)
In this paper a map is introduced showing a hygrothermic classification of climate in the Puebla-Tlaxcala region. This map was produced by using effective criterias: these were on the one hand the tropical altitudinal belts of temperature including the number of freeze-and-thaw days and on the other hand the length of the humid period as well as the mean annual precipitation and its spatial distribution. The interdependence of the thermal and hygric principal components results in 16 principle hygrothermic climatic types, if subclassifications are considered in 24 climate regions. This leads to an index for the potential ecological value of the various regions particularly in regard to their natural vegetation and also to definite statements about agriculture and forestry. In addition climatological field work was carried out which brought to light a number of special phenomena, which are indicated on the map by appropriate symbols. The map shows the transition from warm tropical to cold tropical climate caused mainly by the difference in relief between the basin and mountain regions as well as the formation of dry and humid areas which in part can be understood as the immediate consequence of differences in exposure.